2022
DOI: 10.1590/0102-311x00287820
|View full text |Cite
|
Sign up to set email alerts
|

Genetic, sociodemographic and lifestyle factors associated with serum 25-hydroxyvitamin D concentrations in Brazilian adults: the Pró-Saúde Study

Abstract: This study aims to investigate factors associated with serum 25-hydroxyvitamin D [25(OH)D] concentration in Brazilian adults considering sociodemographic and lifestyle factors, as well as vitamin D-related single nucleotide polymorphisms (SNPs). This is a cross-sectional study (n = 491; 34-79y; 251 women), nested within a prospective cohort (Pró-Saúde Study). Associations between serum 25(OH)D and sociodemographic characteristics, diet, use of supplement, physical activity, season of blood collection, body fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
1
0
Order By: Relevance
“…In spite of the small amount of supplemental vitamin D used in our study (200 IU/day), we cannot rule out the possibility that vitamin D per se (or as adjuvant) had some effect on changes in adipose tissue. In fact, several epidemiological studies have reported an association between low vitamin D status and higher measures of fat deposition (Bezerra et al, 2022; Lehtinen‐Jacks et al, 2016; Rafiq et al, 2019); potential explanations include sequestration and storage of vitamin D by adipose tissue and less exposure to sunlight in individuals with obesity (Vimaleswaran et al, 2013). However, experimental data rise evidence of a causal relationship in the opposite direction, suggesting that interventions with supplemental vitamin D have the potential to contribute to decrease fat accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of the small amount of supplemental vitamin D used in our study (200 IU/day), we cannot rule out the possibility that vitamin D per se (or as adjuvant) had some effect on changes in adipose tissue. In fact, several epidemiological studies have reported an association between low vitamin D status and higher measures of fat deposition (Bezerra et al, 2022; Lehtinen‐Jacks et al, 2016; Rafiq et al, 2019); potential explanations include sequestration and storage of vitamin D by adipose tissue and less exposure to sunlight in individuals with obesity (Vimaleswaran et al, 2013). However, experimental data rise evidence of a causal relationship in the opposite direction, suggesting that interventions with supplemental vitamin D have the potential to contribute to decrease fat accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…Several polymorphisms in CYP2R1 and CYP24A1 were associated with serum vitamin D and vitamin D insufficiency in a study of ~800 young people from deprived areas in Salvador, Bahia (17). In contrast, smaller studies investigating the same genes, but different SNPs and populations did not find any effect (18)(19)(20).…”
Section: Other Genesmentioning
confidence: 92%